2021
DOI: 10.1097/ico.0000000000002759
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Patient Satisfaction After Corneal Neurotization

Abstract: The aim of this study was to assess clinical outcomes of corneal neurotization (CN) and determine patient perception of postoperative results. Methods:This was a retrospective study involving 29 eyes in 28 patients who underwent CN. Chart review data included demographic and clinical history; ophthalmic examination including visual acuity, ocular surface quality, and corneal sensation; surgical technique; and postoperative course. Subjective self-reported patient outcomes of surgical success were also assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The authors suggest that considering these complications, alternative mediums for nerve reconstruction should be explored [ 70 ]. Rafailov et al showed in a retrospective study high patient satisfaction and minimal postoperative pain and morbidity [ 71 ]. Catapano et al looked at sensory and functional morbidity following sural nerve harvest in pediatric patients (14 cases).…”
Section: Corneal Neurotization—surgical Techniquesmentioning
confidence: 99%
“…The authors suggest that considering these complications, alternative mediums for nerve reconstruction should be explored [ 70 ]. Rafailov et al showed in a retrospective study high patient satisfaction and minimal postoperative pain and morbidity [ 71 ]. Catapano et al looked at sensory and functional morbidity following sural nerve harvest in pediatric patients (14 cases).…”
Section: Corneal Neurotization—surgical Techniquesmentioning
confidence: 99%